Performa Pertumbuhan Ikan Kerapu Bebek Cromileptes Altivelis Yang Dibudidayakan Dengan Sistem Keramba - Iskandar, Andri; Mulya, M. Arif; Rifqi, Ahmad Tsaqifur; Putro, Dwi Handoko; Rifaie, Arif Rahman (Fakultas Pertanian Universitas Samudra, 2022)
Humpback grouper Cromileptes altivelis is seawater that lives in tropical waters, especially in Indonesia. This fish has high economic value and is the most expensive grouper fish in Indonesia. Humpback grouper seeds can be used as ornamental fish or raised for consumption fish. This study aimed to evaluate the growth performance of humpback grouper cultivated with the cage system. During the maintenance, fish were fed with 1-5% feed ratio. Fish were reared from 30g to 200g in size, and a feed conversion ratio of 2 was obtained with a survival rate of 94%. The fish were started to be given mixed feed with a 3-4% feed ratio, consisting of 15% pellets and 85% fresh fish which had been cut according to the fish mouth opening. The next maintenance starts from fish measuring 200g to reaching 500g with a survival rate of 93%. The profit obtained from harvesting 12 times in one year is IDR 590 587 187 years-1, R/C Ratio 1.80, the payback period is 1.7 years, break event point IDR 376 100 576, BEP unit 895kg, and price cost of production (HPP) Rp 233 312kg-1.